Experimental Study of Enhanced Heat Transfer in a Circular Tube Heat Exchanger with Sinusoidal Baffles - สุวรรณพันธุ์, สุภัทรชัย; แสนคำวงษ์, เอกวุฒิ; ชัยอมฤต, ชาญวิทย์ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
This research presents experimental study on heat transfer enhancement in a constant heat fluxed tube inserted with sinusoidal baffle vortex generator. Several sinusoidal baffle parameters were introduced such as pitch ratio (p/D = PR = 2, 3 and 4) and blockage ratio (e/D = AR = 0.1, 0.2, 0.3 and 0.4). Various relative baffle heights and pitches were tested to investigate the effect of the sinusoidal baffles at on heat transfer and pressure loss. The study was conducted by varying the airflow rate through the tested tube for Reynolds number (Re) from 4,500 - 29,200. Heat transfer and pressure loss were presented in terms of Nusselt number (Nu) and friction factor (f) respectively. The results have shown that the tube with sinusoidal baffle provides a considerable increase in heat transfer and pressure loss in comparison with the smooth tube in the range of 52 - 84 % and 81 - 99 % respectively. The highest Nu/Nu0 and f/f0 were observed at PR = 0.2 and AR = 0.4 in the range of 6.0 - 6.5 times and 82.7 - 95.1 times respectively, whereas the maximum thermal enhancement factor ( ) was at PR = 0.2 and AR = 0.2 of about 1.71 at Re = 4,500.